PENELITIAN EKOLOGI JENIS POHON DI KAWASAN HUTAN BULUNGAN, KABUPATEN BULUNGAN - KALIMANTAN TIMUR - Razali Yusuf (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Studied on species ecology was carried out especiaslly with composition and vegetation structure in mixed dipterocarp forest,Bulungan-East Kalimantan Province.Two sampling plots were set up in 2 selected sites.All trees (dbh>10cm) within each plot were measured, and their height was respectively estimated.The result showed that totally species number from 825 trees at 2 plots recorded 240 species, 127 genera dan 42 families and 33 species among them from family Dipterocarpaceae.That were 22 species meranti (Shorea spp.J, 4 species for kruing Dipterocarpus caudiferus, D. stellatus, D. humeratus, D. hominophyllum), and some from genus Vatica (Vatica vinosa, V. rasak, V. sarawakensis), Hopea bullatifolia, Dryobalanops lanceolata and Parashorea parvifolia. Dipterocarpaceae,Euphorbiaceae and Myristicaceae were some families with have the most species number and some species were dominance representated the family that were Dipterocarpus caudiferus, Dryobalanops lanceolata,Coccoceras borneensis and Knema latifolia.",